Analisis Pengaruh Media Promosi Asuransi Jiwa terhadap Peningkatan Jumlah Nasabah PT. Equity Life indonesia cabang Makassar - Patandean, Eben Haezer; Paridi, Andryanus (Journal of Marketing Management and Innovative Business Review, 2024)
This study aims to determine whether there is an influence between life insurance promotion media on increasing the number of customers of PT. Equity Life Indonesia through multiple linear regression, correlation and determination. The variables used are independent variables, namely Personal Selling promotion media (X1), advertising promotion media (X2) and dependent variables increasing the number of customers (Y). The results of this study, for the influence of personal selling media of 0.918 on increasing the number of customers and on advertising media of 0.923, then the hypothesis states that there is an influence of personal selling and advertising promotion media on increasing the number of customers of PT. Equity Life Indonesia. This can be seen from r = 0.924 meaning the relationship between personal selling media (X1) and advertising (X2) on increasing the number of customers (Y) of 85.5% meaning there is a strong relationship while the rest is influenced by other factors.ing untuk sistem informasi. Abstract ditulis menggunakan Font Times New Roman; size 10; Italic; single space.